Behavioral defects in a DCTN1G71A transgenic mouse model of Perry syndrome. (14th February 2018) - Mishima, Takayasu; Deshimaru, Manami; Watanabe, Takuya; Kubota, Kaori; Kinoshita-Kawada, Mariko; Yuasa-Kawada, Junichi; Takasaki, Kotaro; Uehara, Yoshinari; Jinno, Shozo; Iwasaki, Katsunori; Tsuboi, Yoshio
Highlights: DCTN1 G71A transgenic mice recapitulate symptoms of patients with Perry syndrome. TDP-43 aggregates are not detectable in the DCTN1 G71A mice. DCTN1 G71A transgenic mice represent a novel rodent model of Perry syndrome. Abstract: Perry syndrome is a rare neurodegenerative disease characterized by parkinsonism, depression/apathy, weight loss, and central hypoventilation. Our previously-conducted genome-wide association scan and subsequent studies identified nine mutations in DCTN1, the largest protein subunit of the dynactin complex, in patients with Perry syndrome. These included G71A in the microtubule-binding cytoskeleton-associated protein Gly-rich domain of p150 Glued . The dynactin complex is essential for function of the microtubule-based cytoplasmic retrograde motor dynein. To test the hypothesis that the G71A mutation in the DCTN1 gene is sufficient to cause Perry syndrome, we generated DCTN1 G71A transgenic mice. These mice initially developed normally, but young animals showed decreased exploratory activity and aged animals showed impaired motor coordination. These behavioral defects parallel apathy-like symptoms and parkinsonism encountered in Perry syndrome. TDP-43 aggregates were not detected in the substantia nigra and cerebral cortex of the transgenic mice, although pathological aggregates of TDP-43 have been considered a major neuropathological feature of Perry syndrome. Our study reveals that a single mutation in the DCTN1 gene recapitulates symptoms of Perry syndrome patients, and provides evidence that DCTN1 G71A transgenic mice represent a novel rodent model of Perry syndrome.